1978
DOI: 10.1029/jb083ib11p05420
|View full text |Cite
|
Sign up to set email alerts
|

Vertical seismic noise at very low frequencies

Abstract: We use records from the Project IDA modified LaCoste gravimeters to investigate ground noise at. frequencies from 1 to 10 mHz. At most sites the level between 2 and 10 mHz is nearly flat and close to 2 × 10−18 m2 s−3 Much higher values which are observed at island and coastal stations are due to loading by waves trapped along the shore. Data from the superconducting gravimeter at Piñon Flat Geophysical Observatory show that the noise power increases as ƒ−2.7 for frequencies between 1 and 0.001 mHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 13 publications
4
38
0
Order By: Relevance
“…As can be seen from the figure, the noise level of the IDA network's Lacoste-Romberg gravimeters is only slightly above that of the superconducting instrument used in the Agnew & Berger (1978) study. Thus, by stacking the IDA records we can expect to achieve a noise level comparable to that attained in some of the previously mentioned studies using the superconducting instruments.…”
Section: Data Reduction and Earthquake Selectionmentioning
confidence: 86%
See 2 more Smart Citations
“…As can be seen from the figure, the noise level of the IDA network's Lacoste-Romberg gravimeters is only slightly above that of the superconducting instrument used in the Agnew & Berger (1978) study. Thus, by stacking the IDA records we can expect to achieve a noise level comparable to that attained in some of the previously mentioned studies using the superconducting instruments.…”
Section: Data Reduction and Earthquake Selectionmentioning
confidence: 86%
“…The sloping, heavy line indicates the noise spectrum for a superconducting gravimeter (Agnew & Berger 1978), and the horizontal line indicates the spectral level of a 15ngal oscillatory signal. As can be seen from the figure, the noise level of the IDA network's Lacoste-Romberg gravimeters is only slightly above that of the superconducting instrument used in the Agnew & Berger (1978) study.…”
Section: Data Reduction and Earthquake Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The noise level so estimated is of the order of lO-"m s -~ in a frequency range of the three core modes. Note that in the frequency band between lop3 and lo-' Hz, acceleration amplitude of the ground noise is in general of the order of to 10-'0ms-2 over a 1/3 octave bandwidth (Agnew & Berger 1978;Agnew et al 1986). The above test thus shows that, if the core mode zSz has a high-Q value, it is possible for us to detect it with the Sompi method.…”
Section: Synthetic Testsmentioning
confidence: 89%
“…The ocean effects can also be significant since SY is located near coast (e.g., Agnew and Berger, 1978). Nagata et al (1993) reported a seasonal variation of the amplitudes of ocean tides near SY.…”
Section: Discussionmentioning
confidence: 99%